Novel Quaternary CuAlZnMg High Temperature Shape Memory Alloy (HTSMA) Fabricated by Minor Batch of Zn and Mg Additions - Karaduman, Oktay; Başbağ, Güneş; Özkul, İskender; Canbay, Canan Aksu; Boyrazli, Mustafa (My University, 2023)
Shape memory alloys (SMAs) constitute the second largest commercial smart material class after piezoelectric materials. Different SMA alloy systems or SMAs with miscellaneous functionalities and characteristic properties have been designed for using in different applications until today. High temperature shape memory alloys (HTSMAs) are also widely desired to be used in various smart materials applications. HTSMAs with different functional and characteristic properties are muchly demanded for different tasks to be done by these alloys or devices designed by these alloys. A common and practical way to fabricate SMAs or HTSMAs with different shape memory effect (SME) and other properties is to fabricate them with different alloying compositions and add different additive elements. In this work, a quaternary CuAlZnMg HTSMA with an unprecedented composition consisting minor amount of zinc and magnesium additives was produced by arc melting method. As a result of applying post-homogenization in high ?–phase temperature region and immediate quenching, the microstructural mechanism of a SME property was formed in the produced alloy. After then, to examine SME characteristics of the CuAlZnMg alloy some differential thermal analysis (DTA), microstructural (XRD) and magnetization (VSM) characterization tests were carried out. The DTA results showed that the alloy is a HTSMA exhibiting reverse martensitic transformations at temperature range between 167 °C and 489 °C. The XRD pattern obtained at room temperature revealed the martensite phases formed in the alloy, which phases are the base mechanism of the reversible martensitic transformation (the SME property) of the alloy. The VSM test showed that the alloy exhibit a diamagnetic property with a weak ferromagnetic coercivity contribution.
Keywords: DTA; XRD; Shape memory effect; VSM; Martensitic transformation; CuAlZnMg; High temperature shape memory alloy (HTSMA); Enthalpy